Hubungan Minat Baca dan Kecerdasan Verbal Linguistik dengan Hasil Belajar Tematik Peserta Didik Kelas IV - Kurniawati, Sekar Khota (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Lampung, 2023)
The problem of this research is that reading interest and verbal linguistic intelligence are not optimal yet and the thematic learning outcomes of four grade students at SDN Gugus dokter wahidin sudiro husodo are low. The purpose of this study is to analyze and determine the relationship between reading interest and thematic learning outcomes of four grade students at SDN Gugus Dokter Wahidin Sudiro Husodo and learning reading interest and verbal linguistic intelligence to learn together with thematic learning outcomes of the four grade students of SDN Gugus Dokter Wahidin Sudiro Husodo. The type of research used is correlational research. The population amounted to 95 students with the determination of the sample using probability sampling technique totaling 95. The data collection technique used a questionnaire (questionnaire). The data analysis technique uses product moment correlation and multiple correlation. The results showed that the correlation coefficient value of 0.963 was at the level of